Long‐term efficacy and safety of safinamide as add‐on therapy in early Parkinson's disease. Issue 2 (12th September 2012) - Schapira, A. H. V.; Stocchi, F.; Borgohain, R.; Onofrj, M.; Bhatt, M.; Lorenzana, P.; Lucini, V.; Giuliani, R.; Anand, R.
<x xml:space="preserve">Abstract</x> Background and purpose Safinamide is an α‐aminoamide with both dopaminergic and non‐dopaminergic mechanisms of action in Phase III clinical development as a once‐daily add‐on to dopamine agonist (DA) therapy for early Parkinson's disease (PD). Methods Study 017 was a 12‐month, randomized, double‐blind, placebo‐controlled pre‐planned extension study to the previously reported Study 015. Patients received safinamide 100 or 200 mg/day or placebo added to a single DA in early PD. The primary efficacy endpoint was the time from baseline (Study 015 randomization) to 'intervention', defined as increase in DA dose; addition of another DA, levodopa or other PD treatment; or discontinuation due to lack of efficacy. Safinamide groups were pooled for the primary efficacy endpoint analysis; post hoc analyses were performed on each separate dose group. Results Of the 269 patients randomized in Study 015, 227 (84%) enrolled in Study 017 and 187/227 (82%) patients completed the extension study. Median time to intervention was 559 and 466 days in the pooled safinamide and placebo groups, respectively (log‐rank test; P = 0.3342). In post hoc analyses, patients receiving safinamide 100 mg/day experienced a significantly lower rate of intervention compared with placebo (25% vs. 51%, respectively) and a delay in median time to intervention of 9 days (P < 0.05; 240‐ to 540‐day analysis). Conclusions The pooled data from the safinamide groups failed to reach statistical significance for the primary endpoint of median time from baseline to additional drug intervention. Post hoc analyses indicate that safinamide 100 mg/day may be effective as add‐on treatment to DA in PD.